Evaluation and Management of Neck and Back Pain - Martel, John W.; Potter, Samuel B. (Seminars in Neurology, 2019)
Neck and back pain are common reasons for seeking evaluation and treatment in the emergency department. Within both systems there exist several time-sensitive diagnoses that the emergency provider should be familiar with in order to prevent significant morbidity and mortality. In this article we provide a general overview of these complaints by discussing problems in a systems-based fashion as well as discussing the initial evaluation, work-up, and treatment options for these diagnoses.
Keywords: back pain; neck pain; cauda equina syndrome; spinal epidural abscess; aortic dissection; abdominal aortic aneurysm; vertebral artery dissection